Effect of bile salts on intestinal epithelial function in gilthead seabream (Sparus aurata) - Fuentes, J. (2024)
In the context of modern aquaculture, the effort to reduce the reliance on fishmeal/marine ingredients in fish diets has led to the exploration of plant-based protein sources as potential substitutes, a dietary shift that disrupts the bile acid profile in fish. Therefore, bile salts are being sought as additives. However, artificially increased intestinal levels of bile acids may significantly impact mucosal function. Therefore, here, we explored the regulatory role in the intestine of gilthead sea bream (Sparus aurata) of (i) chenodeoxycholic acid (CDC), (ii) a mixture formed by two bile acids, 3% cholic acid and 97% deoxycholic acid (MIX), and (iii) a conjugated bile salt sodium taurocholate (TC) in Ussing chambers with the epithelial voltage clamp technique. We tested the bile salts in a 50-500 mu g/ml concentration range, and all of them promoted ion absorption. Yet, clear concentration-dependent and more pronounced effects on the ion transport were observed in the posterior intestine. On the other hand, bile salts had no or minor effects on tissue resistance. However, there are indications that the MIX could have adverse effects at high concentrations (500 mu g/ml), promoting a threefold increase in tissue permeability measured using FITC-dextran (4 kD) regardless of the intestinal region, thus suggesting an alteration in intestinal permeability at high bile salt concentrations. The findings from our study emphasize the importance of considering intestinal function when contemplating the possible use of a particular bile salt as a dietary supplement. It appears that bile salts, whether acting individually or in combination, play a pivotal role in orchestrating nutrient absorption by influencing the function of epithelial ion transport. However further research is needed to fully grasp the region-dependent nuances of bile salt effects on ion transport and the ultimate consequences for nutrient absorption in the context of fish aquaculture.